Phosphorus Placement Effects on Phosphorous Recovery Efficiency and Grain Yield of Wheat under No-Tillage in the Humid Pampas of Argentina - Pablo Andrés Barbieri; Hernán René Sainz Rozas; Fernanda Covacevich; Hernán Eduardo Echeverría (International Journal of Agronomy)
No-till (NT) affects dynamics of phosphorus (P) applied. Wheat response to P fertilization can be affected by available soil P, grain yield, placement, rate, and timing of fertilization. Furthermore, mycorrhizal associations could contribute to improving plant P uptake. Three experiments were used to evaluate P rate (0, 25, and 50 kg P ha−1) and fertilizer placement (broadcasted or deep-banded) effects in NT wheat on P recovery efficiency (PRE) yield and arbuscular mycorrhizal colonization (AMC) which was assessed in one experiment. Fertilization increased dry matter (DM) and accumulated P. Broadcasted P produced lower P accumulation than deep-banded P only at tillering. Phosphorus rate decreased PRE, and placement method did not affect it. Grain yield response was increased by P rate (857 and 1805 kg ha−1 for 25 and 50 kg P ha−1, resp.) and was not affected by placement method (4774 and 5333 kg ha−1 for broadcasted and deep-banded, resp.). Deep-banded P depressed root AMC compared with broadcast applications. Highest AMC in P broadcasted treatments could help to explain the lack of differences between placement methods. These results indicate that Mollisol have low P retention capacity. Therefore, broadcasted P could be used as an alternative of fertilizer management for NT wheat.